If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-5(x+12)-13-=-24
We simplify the equation to the form, which is simple to understand
-5(x+12)-13-=-24
Reorder the terms in parentheses
+(-5x-60)-13=--24
Remove unnecessary parentheses
-5x-60-13=--24
We move all terms containing x to the left and all other terms to the right.
-5x=-0+60+13
We simplify left and right side of the equation.
-5x=+73
We divide both sides of the equation by -5 to get x.
x=-14.6
| 4.3b+5=8.1 | | 8.5x^3=79.687x+165.9891 | | 2x^2+7x-2=-2x^2+2x | | x^2+m+7=0 | | 7(x+2)+2=8 | | 5/7n-1=11 | | f(x)=x^5-3x^3+12x | | 3x+3-x=19 | | y+5=12*10 | | (9x+5)=(6x+5) | | 0.2a/4-10=2 | | -3(x-4)-15=-12 | | 2x-3=-7x+105 | | 50+3x^2=2 | | 30/20x=11/20 | | Y-6/y-2 | | f(t)=-16t^2+96t+3 | | a/6+2=4 | | 10x+20y+8=0 | | 26x-26=15 | | -7(7b+4)=119 | | 10x-4=5x+20 | | -3z-2/2=5 | | 6x(x-1)=4x+4 | | 2a/3.1-4=6 | | 3x+14=-16x-2x | | -3(2-8n)=186 | | 4x+3(5-13)=132 | | 2x+3y-8z=89 | | 6x+2(x+7)=-10 | | 3s+8=-10 | | -5(2-5k)-6=134 |